807 The Association between Blood Transfusion and Outcome in Hip Fracture Patients. (19th August 2022) - Brasnic, L; Martin, C; Ward, K; Adam, K; MacLullich, A; Farrow, L
Abstract: Aim: Hip Fractures are endemic in older adults across Europe, with potential increases in incidence expected as the population ages. Management of blood loss and anaemia is a mainstay of care for these patients, but there is still significant debate regarding balance between benefit and risk of liberal versus restrictive transfusion policies. Understanding the association between providing blood products and adverse healthcare outcomes in hip fracture patients is a key component in the transfusion decision-making process. Method: This retrospective cohort study uses national audit data from the Scottish Hip Fracture Audit (SHFA) and the Scottish National Blood Transfusion Service (SNBTS) to examine the association between blood transfusion and important hip fracture process of care measures and healthcare outcomes. Results: A total of 28 461 patient records were included for assessment across 19 acute hospitals. Blood transfusion during admission was associated with a small but statistically significant decrease in survival at both 30 and 60 days. Those receiving blood transfusion during admission were less likely to be mobilised by the end of the 1 st post-operative day, less likely to have a length of stay below the average and had far lower probability of discharge. Conclusion: This study found that blood transfusion is associated with poor healthcare outcomes following hip fracture, even when adjusted for potential confounding factors. This likely reflects the potential harm of perioperative anaemia rather than any direct impact from transfusion. Further work to reduce perioperative blood loss is therefore key to improving important hip fracture outcomes.